Belgium : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Long-term issues continue to dominate the economic policy agenda. The economy is expected to grow at a moderate pace. The challenge from aging is becoming more pressing, calling for sustained fiscal consolidation. The elaboration of a medium-term fiscal framework based on expenditure growth ceilings will help underpin the achievement of budget objectives. The focus on job creation has triggered helpful initiatives but further, comprehensive labor market reform is needed to raise employment rates. An acceleration of product market reform will provide an impetus to growth.